Discovery of new A- and B-type laxaphycins with synergistic anticancer activity. Issue 9 (15th May 2018) - Cai, Weijing; Matthew, Susan; Chen, Qi-Yin; Paul, Valerie J.; Luesch, Hendrik
Graphical abstract: Abstract: Two new cyclic lipopeptides termed laxaphycins B4 (1 ) and A2 (2 ) were discovered from a collection of the marine cyanobacterium Hormothamnion enteromorphoides, along with the known compound laxaphycin A. The planar structures were solved based on a combined interpretation of 1D and 2D NMR data and mass spectral data. The absolute configurations of the subunits were determined by chiral LC-MS analysis of the hydrolysates, advanced Marfey's analysis and 1D and 2D ROESY experiments. Consistent with similar findings on other laxaphycin A- and B-type peptides, laxaphycin B4 (1 ) showed antiproliferative effects against human colon cancer HCT116 cells with IC50 of 1.7 µM, while laxaphycins A and A2 (2 ) exhibited weak activities. The two major compounds isolated from the sample, laxaphycins A and B4, were shown to act synergistically to inhibit the growth of HCT116 colorectal cancer cells.